An ecological approach to the development of an active aging measurement in urban areas (AAMU) - Azadeh Lak; Parichehr Rashidghalam; S. Nouroddin Amiri; Phyo K. Myint; Hamid R. Baradaran (BMC, 2021)
Abstract Background An essential element in the process of "aging well" is the concept of Active Aging (AA). To propose an operational definition of Active Aging, the present study seeks to develop a new measurement tool through an ecological approach. The aim is to recognize significant indicators that play a role in assessing AA in urban areas. Methods This study was conducted through a two-phase process of consensus-building: 1) identifying a set of indicators that were likely candidates for inclusion based on literature review, and 2) a two-round modified Delphi survey using an international panel of academic experts in environmental sciences and gerontology to achieve consensus on the importance of the extracted indicators and validate the items. The panelists were asked to complete a researcher-developed questionnaire with an 11-point Likert scale based on the indicators derived in phase 1. Finally, the Delphi survey's valid indicators and criteria were utilized to develop the measurement tool. Results At the outset, a list of 111 indicators of AA was prepared through the desk study. A panel of 22 experts reviewed the extracted items and arrived at a consensus on 99 items in the first round and finalised in the second round. Thematic analysis of the panelists' open-ended responses revealed new concepts that would be explicitly considered by the consensus group. This developed measurement scale consists of five domains, i.e., individual, spatial, socio-economic, governance, and health-related, which contain 15 criteria and 99 indicators. Conclusions The present researchers have developed the active aging measure for urban settlements (AAMU), which can be used both by policy-makers and as an informal self-reported statement among the elderly. AAM's results in the elderly's residential environmental communities can improve policy-making to address urban design to sustain an active, healthy life among older people in urban environments.